Shifting the refugee narrative? An automated frame analysis of Europe's 2015 refugee crisis. Issue 11 (18th August 2017) - Greussing, Esther; Boomgaarden, Hajo G.
ABSTRACT: In 2015, Europe faced the arrival of over 1.25 million refugees fleeing from war-affected countries. The public mainly learned about this issue through domestic media. Through the use of computer-assisted content analysis, this study identifies the most dominant frames employed in the coverage of refugee and asylum issues between January 2015 and January 2016 in six Austrian newspapers ( N = 10, 606), particularly focusing on potential differences between quality and tabloid media, and on frame variations over time. The findings reveal that, apart from administrative aspects of coping with the arrivals, established narratives of security threat and economisation are most prominent. Humanitarianism frames and background information on the refugees' situation are provided to a lesser extent. During the most intense phases of the crisis, the framing patterns of tabloid and quality media become highly similar. Media coverage broadens to multiple prominent frames as issue salience sharply increases, and then 'crystallises' into a more narrow set. In sum, the results confirm a predominance of stereotyped interpretations of refugee and asylum issues, and thus persisting journalistic routines in both, tabloid and quality media, even in times of a major political and humanitarian crisis.